Effectiveness of using a bar model in solving story problems for elementary school students - Erna Yayuk; Beti Istanti Suwandayani; Alfiani Athma Putri Rosyadi; Dyah Worowirastri Ekowati; Agung Deddiliawan Ismail (Research and Development in Education (RaDEn), 2024)
One of difficulty student in study mathematics that is how to finish math narrative text. The purpose of research this that is for describe about effectiveness of the bar model for finish math narrative text for school base. Type of research used in study that is descriptive qualitative, with 22 of students in third grade as a research subject. Moreover, this research was conducted in State Elementary School 01 of Beji Junrejo Disctrict, Batu – East Java. Data collection techniques use observation, interviews and tests. Furthermore from the data obtained analyzed in a way qualitative with use stage: data reduction, data presentation, and withdrawal data conclusions. The research results show that the bar model is very effective help student in finish math narrative text this elementary school student capable draw a bar model for represent mark in mathematics. This is can help they in answer question with more easy and doable develop number sense ability.